Continuing Education in Mental Health: Critical Moments to Analyze Group Process - Silva, Gabriela Martins; Ness, Ottar (Paidéia (Ribeirão Preto), 2018)
In Brazilian context, literature points to Continuing Education in Health (CEH) policy as a means to actualize the Psychiatric Reform. Although it is also a challenge considering its proposal of close connectedness with each context in which it occurs. This study aimed to understand how mental health professionals learn together in CEH-processes, identifying and understanding conversational transformations that occurred in the interactional process. An educational process inspired by the CEH policy was then carried out with a group of eight professionals from a Psychosocial Care Center. This process was analyzed from the notion of critical moments, with a social constructionist stance. In doing so, the critical moment “Sharing the Feeling of Standstill” was delimited considering its effects on the conversational process. With this, it is argued that, even in conversations that seem saturated by problems, it is possible to identify generative moments, as a relational achievement, through dialogue.